The Opportunity of Augmented Reality (AR) Technology as an Immersive Learning Medium in Physics Subjects - Sigit Dwi Saputro; Naelur Rohmah (Universitas Trunodjoyo Madura, 2026)
Deep learning demands high cognitive engagement and contextual understanding of concepts. Learning media that is able to present contextual experiences is believed to improve the quality of deep learning. Deep Learning in this research is the implementation of the curriculum that has been determined by the Ministry of Primary and Secondary Education of the Republic of Indonesia. Augmented Reality (AR) is emerging as a potential medium due to its ability to visualize abstract concepts interactively and contextually. This study conducted a literature review of 20 Scopus indexed articles in the last 5 years (2019–2024) that examined the implementation of AR in physics learning, with the exception of articles that are more than 5 years old and articles outside the field of physics. The analysis shows that AR significantly improves concept understanding, learning engagement, and the ability to apply physics concepts in real contexts. Based on various studies, the use of Augmented Reality (AR) in physics learning has been proven to support deep learning through increased concept understanding and critical thinking (mindful learning), visualization of abstract concepts that are more contextual (meaningful learning), and increased motivation, engagement, and joyful learning experiences (joyful learning). The implications of this research are as a reference for researchers to test the impact of using AR media. As future research needs to test the contribution of AR to deep learning